Hydrogen storage engineering in PHE-graphene monolayer via potassium (K) decoration - Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Ye, Lingyu; Sambrano, Julio R. [UNESP]; Chen, Xihao (Elsevier, 2025)
The increasing demand for ecofriendly and efficient energy sources accelerates the transition from fossil fuels to hydrogen (H2), which requires advances in production, transportation, and storage technologies. This study investigates the functionalization of PHE-graphene via potassium (K) decoration. A comprehensive analysis of the K@PHE-graphene system revealed a transition from metallic to semiconductor character due to charge transfer from K adatoms (+0.89|e|). Molecular dynamics simulations confirmed the retention of K atoms at their preferred adsorption sites, ensuring the structural integrity of the substrate. K@PHE-graphene complex has an exceptional adsorption capacity of 7.47 wt%, exceeding the DOE target of 5.5 wt%. Thermodynamic analysis also highlighted an optimal storage conditions, achieving maximum capacity between 100-150 K at low pressures (0–20 atm) and maintaining efficiency at higher pressures (40–60 atm) even at elevated temperatures. These findings establish K@PHE-graphene as a promising candidate for reversible hydrogen storage applications.
Keywords: 2D material; Energy; Hydrogen; PHE-graphene; Storage